2021
DOI: 10.3390/ijerph18084355
|View full text |Cite
|
Sign up to set email alerts
|

Planned Relocation and Health: A Case Study from Fiji

Abstract: In Fiji, low-lying coastal villages are beginning to retreat and relocate in response to coastal erosion, flooding and saltwater intrusion. Planned relocation is considered a last resort as a form of adaptation to the impacts of climatic and environmental change. The health impacts of planned relocation are poorly understood. This paper draws on data from multi-year research with residents of the iTaukei (Indigenous) Fijian village of Vunidogoloa. We used qualitative research methods to examine experiences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…There are also emerging concerns that managed retreat and similar policies are being used to disconnect Indigenous communities from their land, community, cultures and traditional knowledge [75,150]. Negative social and health impacts and a need to centre human rights feature strongly in Oceania case studies [106,107,152,153], but also in the United States, where Solecki & Friedman [154] offer an analysis of the relationships between climate risks, adaptation actions and the impacts of both on well-being and mental health for coastal residents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also emerging concerns that managed retreat and similar policies are being used to disconnect Indigenous communities from their land, community, cultures and traditional knowledge [75,150]. Negative social and health impacts and a need to centre human rights feature strongly in Oceania case studies [106,107,152,153], but also in the United States, where Solecki & Friedman [154] offer an analysis of the relationships between climate risks, adaptation actions and the impacts of both on well-being and mental health for coastal residents.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority explore these factors at the state scale via localized/regional case study examples. This trend is reflected across a range of geographies, including the United States [57,58,[69][70][71][72][73][74][75][76][77][78]; South America [79,80]; Canada [81,82]; Western European countries including France, Germany, Austria, and Sweden [83][84][85][86][87][88][89][90][91][92][93]; the United Kingdom and Ireland [56,94,95]; and the South Asia and Asia-Pacific region [20,21,52,82,85,[96][97][98][99][100][101][102][103][104][105][106][107]. Almost all of these papers are concerned with understanding retreat from coastal or lowlying areas, with the exception of some o...…”
Section: (B) Governance Policy and Institutional Factorsmentioning
confidence: 99%
“…Until now, only a few I-Taukei (Indigenous) villages have been entirely or partially moved to new locations inland. One of them is the village of Vunidogoloa on Fiji's second largest island Vanua Levu, which has been the focus of several empirical studies (e. However, although the new location is only a short walk away from the former coastal settlement, many villagers reported that they missed their connection to the ocean and to ancestral land (Piggott-McKellar et al 2019;McMichael and Powell 2021). As the following quote from a female resident demonstrates, some villagers also reported a loss of agency as they could not participate in decision-making about the relocation: 'We were not consulted.…”
Section: Climate-related Planned Relocation In Fiji: Experiences Of I...mentioning
confidence: 99%
“…g.,Bertana 2020;McMichael and Powell 2021;Piggott-McKellar et al 2019). The village community was relocated around two kilometres inland because it faced frequent floods and was increasingly exposed to coastal erosion that threatened their land and village infrastructure(McMichael and Powell 2021).…”
mentioning
confidence: 99%
“…These extreme natural events threaten the livelihoods of coastal people in Fiji and other PICTs. In 2014, the people of Vunidogoloa Village in the province of Cakaudrove were relocated (in a planned effort) from their traditional home due to coastal erosion and other socioeconomic factors, including limited access to services and its geographic isolation from road and public transportation (McMichael and Powell, 2021). However, there are instances where such relocation of villagers was unplanned, like the Tukuraki Village in the Ba Province (Coca, 2021).…”
Section: Introductionmentioning
confidence: 99%